A remix-oriented approach to promoting student engagement in a long-term participatory learning program. (July 2017) - Liu, Chen-Chung; Chen, Wei-Chen; Lin, Hung-Ming; Huang, Yun-Yin
Abstract: Researchers and educators continuously remark on the importance of integrating creativity into the learning process. This study proposes a creativity approach to facilitating participatory learning for the sustained engagement of young learners based on the principle of remix practice, which consists of learning to generate online artefacts, endless hybridization and scaffolding. This study investigated students' engagement in and perceptions of the creative learning process during a two-year participatory learning program. Data collected included students' flow perceptions during a 39-week activity, their motivation and creative self-efficacy before and after the intervention, as well as their creative products. The findings indicated that the remix-oriented approach led to a higher level of intrinsic motivation and sustained flow compared to a model-based approach, especially interest and curiosity, in this participatory learning program. The approach also helped the students to perceive a significant increase in their level of creative self-efficacy associated with strategies to generate creative ideas. The results of this study suggest that the principle of remix practice is helpful for leveraging knowledge acquisition and the creative nature of participatory learning activities to sustain student engagement in participatory learning programs. Highlights: The integration of creativity into the learning process requires more evidence-based research. A remix-oriented approach was implemented for the sustained engagement during a two-year program. The creativity approach led to a higher level of intrinsic motivation and sustained flow. Students perceived a significant increase in their level of creative self-efficacy. Endless hybridization is helpful for leveraging knowledge acquisition and creative learning process.